Dalihan Na Tolu as a Model for Resolving Religious Conflicts in North Sumatera: An Anthropological and Sociological Perspective - Harahap, Anwar Sadat; Mulyono, Hardi; A. Nuzul, A. Nuzul; Milhan, Milhan; Siregar, Taufik (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
It is undeniable that there are various social conflicts in Indonesia which involve various groups of people such as the religious conflict in Poso (2001), in Sampit (2001), in Ambon (2002) and others. Most of them were caused by uncertain, unfair, and misused regulations on keeping people’s religious tolerance. It was also caused by the lack of people’s empowerment in keeping religious tolerance. This study aims to examine dalihan na tulo as a mechanism for resolving religious conflicts in the Mandailing community, North Sumatra. This research uses juridical empirical methods, consisting of anthropological and sociological law approaches. Data were collected by means of interviews and literature studies. The result of the research showed that Dalihan na Tolu tradition based-model of maintaining religious tolerance and resolving conflicts in religious believers was done by using the philosophy of Dalihan na Tolu, Pastak-pastakni Paradaton, Uhum dohot Patik and Tutur dohot Poda. There are three types of negotiation system in resolving the conflicts: Tahi Dalihan na Tolu, Tahi Godang Parsahutaon, and Tahi Godang Haruaya Mardomu Bulung (big negotiation among the neighboring villages). Anthropologically and sociologically that the Mandailing community has proven successful in using adat as a resolution of religious conflicts, so as to create peace and order as a function of law in society.